Characterization of Influenza A and B Viruses Circulating in Southern China During the 2017–2018 Season - Yan, Yuqian; Ou, Junxian; Zhao, Shan; Ma, Kui; Lan, Wendong; Guan, Wenyi; Wu, Xiaowei; Zhang, Jing; Zhang, Bao; Zhao, Wei; Wan, Chengsong; Shi, Weifeng; et al. (Frontiers in Microbiology, 2020)
The trivalent seasonal influenza vaccine was the only approved and available vaccine during the 2016-2018 influenza seasons. It did not include the B/Yamagata strain. In this study, we report an acute respiratory disease outbreak associated with influenza B/Yamagata infections in Guangzhou, Southern China (January through March, 2018). Among the 9914 patients, 2241 (22.6%) were positive for the influenza B virus, with only 312 (3.1%) positive for the influenza A virus. The influenza B/Yamagata lineage dominated during this period in Southern China. The highest incidence of influenza A virus infection occurred in the children aged 5-14 years. In contrast, populations across all age groups were susceptible to the influenza B virus. Phylogenetic, mutations, and 3D structure analyses of hemagglutinin (HA) genes were performed to assess the vaccine-virus relatedness. The recommended A/H1N1 vaccine strain (A/Michigan/45/2015) during both 2017-2018 and 2018-2019 was antigen-specific for these circulating isolates (clade 6B.1) in Spring 2018. An outbreak of influenza B/Yamagata (clade 3) infections in 2018 occurred during the absence of the corresponding vaccine during 2016-2018. The recommended influenza B/Yamagata vaccine strain (B/Phuket/3073/2013) for the following season (2018-2019) was antigen-specific. Although there were only a few influenza B/Victoria infections in Spring 2018, five amino acid mutations were identified in the HA antigenic sites of the 19 B/Victoria isolates (clade 1A), when compared with the 2016-2018 B/Victoria vaccine strain. The number was larger than expected and suggested that the influenza B HA gene may be more variable than previously thought. One of the mutations (K180N) was noted to likely alter the epitope and to potentially affect the viral antigenicity. Seven mutations were also identified in the HA antigenic sites of 2018-2020 B/Victoria vaccine strain, of which some or all may reduce immunogenicity and the protective efficacy of the vaccine, perhaps leading to more outbreaks in subsequent seasons. The combined epidemiological, phylogenetic, mutations, and 3D structural analyses of the HA genes of influenza strains reported here contribute to the understanding and evaluation of how HA mutations affect vaccine efficacy, as well as to providing important data for screening and selecting more specific, appropriate, and effective influenza vaccine candidate strains.